2002
DOI: 10.4049/jimmunol.168.11.5764
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Impairment of IFN-γ Secretion in Suppressed HIV-Infected Patients Despite Mature NK Cell Recovery: Evidence for a Defective Reconstitution of Innate Immunity

Abstract: The impairment of NK cell functions in the course of HIV infection contributes to a decreased resistance against HIV and other pathogens. We analyzed the proportion of mature and immature NK cell subsets, and measured subsets of IFN-γ and TNF-α-producing NK and T cells in viremic or therapy-suppressed HIV-infected subjects, and noninfected control donors. Viremic HIV+ individuals had significantly lower proportions of mature CD3−/CD161+/CD56+ NK cells and of IFN-γ-producing NK cells compared with noninfected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
95
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 51 publications
6
95
2
1
Order By: Relevance
“…A significantly lower proportion of CD3 Ϫ CD16 ϩ CD56 ϩ NK cells are found in HIV-infected patients with uncontrolled HIV replication (6), in comparison to patients with therapeutically suppressed HIV viremia. Moreover, NK cell activity is impaired by both a reduction of NK cell number and a reduction in NK cell cytolytic function (27,44,69).…”
Section: Discussionmentioning
confidence: 96%
“…A significantly lower proportion of CD3 Ϫ CD16 ϩ CD56 ϩ NK cells are found in HIV-infected patients with uncontrolled HIV replication (6), in comparison to patients with therapeutically suppressed HIV viremia. Moreover, NK cell activity is impaired by both a reduction of NK cell number and a reduction in NK cell cytolytic function (27,44,69).…”
Section: Discussionmentioning
confidence: 96%
“…The perturbations observed in the NK cell compartment during chronic HIV-1 infection include the overall increased activation of NK cells, the early loss of CD3 Ϫ CD56 bright NK cells, the accumulation of anergic CD3 Ϫ CD56 Ϫ CD16 ϩ NK cells (6,10), and the impairment of their cytotoxic capacity (6,9,10,56) and cross-talk with DCs (11). The mechanisms underlying these numeric and functional NK cell perturbations observed during viremic HIV-1 infection are not understood.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying these numeric and functional NK cell perturbations observed during viremic HIV-1 infection are not understood. However, suppression of HIV-1 viremia by antiretroviral therapy results in at least a partial reconstitution of NK cell numbers and function (6,9,55). Recently, it has been demonstrated that ssRNA derived from HIV-1 LTR can activate DCs via TLR7/8 (2,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous experimental and clinical studies have documented this finding (6)(7)(8). The negative effects of HIV on NK cells are pervasive, involving both the quantity and functions of NK cells.…”
mentioning
confidence: 99%